Strengthening the School Literacy Movement: The Utilization of Literacycloud.com Technology to Improve Students' Interest in Reading - Faizah, Rohmatul; Baedowi, Ahmad; Fadil, Cholid; Rifqi Rizqullah Ghozalie, Mohammad (CV. Inara, 2022)
A great nation is a nation that not only utilizes its natural resources but also develops other potentials such as reading and writing as a bridge of civilization from one generation to another. Nowadays, technology is commonly used in all fields, including education, to increase the reading interest among students that are still very low. The School Literacy Movement (Gerakan Literasi Sekolah or GLS) is part of the implementation of the Regulation of the Minister of Education and Culture Number 23 the Year 2015 concerning